2021
DOI: 10.3390/educsci11010025
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Emotional Intelligence and Personality Traits of University Finance Students

Abstract: Studies on financial behavior indicate that emotional intelligence (EI) and personality traits (PTs) explain much of the bias in financial activity. This study aims to identify in which dimensions of theEI and PTs of university students in finance further training is needed to avoid financial behavior bias. To this end, the EI and PT levels of a sample of university finance students and financial industry professionals were compared using the Trait Emotional Intelligence Questionnaire (TEIQue) and Big Five Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Individuals with conscientious traits are more likely to be selfdisciplined highly competent, and exhibit active participation in decision making (Picone 2021;Zahera and Bansal 2018). Existing literature proves the linkage between conscientiousness trait and behaviour biases (Rosales-Pérez et al 2021;Lin 2011a, b). Studies (like Baker et al 2021;Zaidi and Tauni 2012) inspect the effect of personality traits on overconfidence bias.…”
Section: Association Between Conscientiousness Trait and Behaviour Bi...mentioning
confidence: 99%
“…Individuals with conscientious traits are more likely to be selfdisciplined highly competent, and exhibit active participation in decision making (Picone 2021;Zahera and Bansal 2018). Existing literature proves the linkage between conscientiousness trait and behaviour biases (Rosales-Pérez et al 2021;Lin 2011a, b). Studies (like Baker et al 2021;Zaidi and Tauni 2012) inspect the effect of personality traits on overconfidence bias.…”
Section: Association Between Conscientiousness Trait and Behaviour Bi...mentioning
confidence: 99%
“…An example of this is the study that found that women are less likely to be paid even if they already have financial experience and avoid risk. (Rosales-Pé rez et al, 2021). Lessons from the investment reliance field usually focus on one country at a time.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a degree of the unit can absorb these emotions and thoughts, and strategically use them to achieve the alignment of goals, and to effectively organize the negative and positive emotions and the best of possibly of others [4]. In [5] describe a suitable representation of the importance of emotional intelligence. He points out that the benefits of emotional intelligence to motivate people, to help in the control of impulsivity, and to the right, and the turn-on of the people are in situations where they face barriers to success.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The skill model that focuses on the ability of a person to research the emotional details he or she has used to navigate a social space. [5] Goleman's original model can now be considered a hybrid model that combines what has been modeled separately such as EI capability and trait EI. Recent research has focused on emotional awareness, which refers to the provision of emotional states based on the perception of visual and audible non-verbal cues.…”
Section: Introductionmentioning
confidence: 99%